2019
DOI: 10.31234/osf.io/qyt95
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Japan Religious?

Abstract: The popular image of Japan and religion presents something of a paradox. On the one hand, large cross-cultural surveys frequently present Japan as a country of non-believers, where only 10-15% of the population self-identify as religious and the vast majority rank religion as being of little importance to their lives. Yet, any visitor to Japan is likely to be struck by the sheer number of Shinto shrines and Buddhist temples that dot the landscape and the diverse array of festivals (matsuri) that are performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Therefore, it is possible that for some of our participants this music did not cue normative behavior typical for the targeted religious affiliation. Second, religion in Japan, as elsewhere in Asia, is typically regarded as non-exclusive and has been described as having a 'practical' orientation wherein adherence to religious beliefs is seen as of secondary importance to ritual practices [37,39,70], potentially confounding the measure of religiosity. For instance, Kavanagh and Jong [39], recently demonstrated that while only 10% of 1,000 Japanese respondents self-identified as religious, 34% in the same sample identified as Buddhist, 5% as Shinto, and 33% endorsed the existence of God.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that for some of our participants this music did not cue normative behavior typical for the targeted religious affiliation. Second, religion in Japan, as elsewhere in Asia, is typically regarded as non-exclusive and has been described as having a 'practical' orientation wherein adherence to religious beliefs is seen as of secondary importance to ritual practices [37,39,70], potentially confounding the measure of religiosity. For instance, Kavanagh and Jong [39], recently demonstrated that while only 10% of 1,000 Japanese respondents self-identified as religious, 34% in the same sample identified as Buddhist, 5% as Shinto, and 33% endorsed the existence of God.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we broaden the generalizability of this research by diversifying the sample, adding an East Asian (Japan) site to our sample in which the religious traditions represented are non-exclusive and focus more on practice (orthopraxy) than belief (orthodoxy) [36,37]. Given the population size of Japan (126.2 million: [38]) and the prevalence of orthopraxic religion in East Asia [39], adding a Japanese sample enables further examination of the generalizability of the hypothesized religious priming relationships. For a detailed summary of the differences between the design employed in this paper and the design used in Lang et al [4], see S1 Table H in S1 File.…”
Section: Introductionmentioning
confidence: 99%
“…Some people visit Kodaiji Temple specifically to see Mindar, but since the temple is already well-established, many people come to the temple with no intent of visiting Mindar. It is worth noting that, unlike in Western countries, Japanese are less likely to consider themselves loyal to any single tradition such as Buddhism or Shinto (Kavanagh & Jong, 2019;Reader, 1991). They may participate in activities associated with both religious traditions or other religious traditions.…”
Section: Sample and Settingmentioning
confidence: 99%
“…The Buddhist aspects are traced back to celebrations derived from the Yulanpen Sutra, which recounts the tale of Mokuren, a disciple of the Buddha, who visualizes his deceased mother's suffering in the afterlife and seeks the Buddha's guidance for her relief [15]. Within Japan's non-exclusive, syncretic, and orthopraxic religious environment [16,17] the Bon Festival manifests as a mixture of religious traditions, incorporating aspects of Buddhism, Shinto, and local folk practices [18]. Here, the emphasis is more on the correct performance of ritual acts, reflective of Japan's orthopraxic tendencies, rather than a strict adherence to a particular belief system [19].…”
Section: Introductionmentioning
confidence: 99%